An Occult Malignancy Behind a Demyelinating Disease: POEMS Syndrome. (October 2016) - Lo Presti, Saberio; Kanagarajah, Prashanth; Pirela, Daniela; Morlote, Diana; Cusnir, Mike
We report a case of a 38-year-old man presenting with bilateral lower extremity weakness and paresthesias that progressed during a 4-month period to severe polyneuropathy forcing the patient to be bed bound. Throughout his multiple hospitalizations, he was treated erroneously for chronic inflammatory demyelinating polyneuropathy, without significant improvement in his symptoms. In addition, he developed hepatosplenomegaly (organomegaly); endocrinopathies such as diabetes mellitus, central hypogonadism, and hypothyroidism; monoclonal spike evidenced in the serum electrophoresis; and hyperpigmentation of skin, altogether consistent with POEMS syndrome. During his last hospitalization he developed excruciating pain on his left hip, and imaging revealed the presence of a 9 × 6 cm osteolytic mass with sclerotic rim in the left acetabulum. Biopsy of the mass confirmed an isolated IgG lambda plasmacytoma. The patient received radiation to his left acetabular lesion followed by left hip replacement. Subsequently, the patient underwent autologous bone marrow transplant. Eighteen months after his initial presentation, he had satisfactory clinical response and is functional without significant limitations. POEMS syndrome is a rare paraneoplastic syndrome secondary to an underlying plasma cell disorder, which can oftentimes be overlooked and misdiagnosed. The median age of presentation is 51 years, and only 31% of the cases occur in fairly young patients under the age of 45 as evidenced in this case. As clinicians, we should be aware of the constellation of features associated with POEMS syndrome and be able to recognize them promptly.